2016
DOI: 10.1515/orhu-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Nest site characteristics of the Great-spotted Woodpecker in a bottomland riparian forest in the presence of invasive tree species

Abstract: This study was carried out in Hungary, in an old unmanaged riparian poplar-willow forest during the breeding seasons of 2014 and 2015. The occurrence of two invasive tree species, the green ash and boxelder, is significant in the study area, which influences negatively the populations of native riparian tree species in Central Europe. We studied Great-spotted Woodpecker nest sites in the presence of these invasive species. Throughout the study period, eight and twelve nesting cavity trees were mapped. Trees we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This finding supports the enemy release hypothesis (Keane & Crawley, 2002). The reduction in the quantity of softwoods in the canopy layer, meanwhile, can exert a significant effect on the whole floodplain forest community (Ónodi & Winkler, 2016).…”
Section: Conservation Consequencesmentioning
confidence: 99%
“…This finding supports the enemy release hypothesis (Keane & Crawley, 2002). The reduction in the quantity of softwoods in the canopy layer, meanwhile, can exert a significant effect on the whole floodplain forest community (Ónodi & Winkler, 2016).…”
Section: Conservation Consequencesmentioning
confidence: 99%
“…In the framework of this baseline survey, we studied foraging on living trees, a subject which is generally uncommon in woodpecker-related research. Nonetheless, some previous studies have indicated that Great Spotted Woodpeckers are often associated with living trees (Török 1990, Farris & Zack 2005, Pasinelli 2007, Ónodi & Csörgő 2014, Ónodi & Winkler 2016, Kosiński et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant European species, the Great Spotted Woodpecker (Dendrocopos major), is often categorized as a keystone species, especially in suboptimal habitats, where there is invariably a lack of natural cavities (Pasinelli 2007). However, this species is a major nest predator of cavity-nesting songbirds and therefore, its keystone role is sometimes considered as controversial (Wesolowski 2007, Ónodi & Winkler 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the niche overlap analysis showed that Picumnus cirratus and medium-sized woodpeckers have similar use of tree species, but differ from the tree species used by Campephilus leucopogon. Therefore, be tween the smaller and medium-sized excavators, there may be competition for the use of available tree species (Kosinski & Winiecki 2004, Pasinelli 2007, Ónodi & Winkler 2016. The intermediate values from Levin's analyses suggest that woodpeckers do not use a single tree species, but instead specialize in use of several tree species (Krebs 1998).…”
Section: Discussionmentioning
confidence: 99%